ANALISA DAN PERANCANGAN PENGUSIR NYAMUK DBD DENGAN SENSOR ULTRASONIK ARDUINO DAN INFRA MERAH - Elliarini isabela (INFOKOM (Informatika & Komputer), 2019)
Dengue fever is a contagious desease which is still a public health problem in Indonesia.The purpose of this study was to prevent the spread of the epidemic of dengue fever by using infrared light.Fogging is an Old way to eradicate dengue an it’s still considered a lot off problems when eradicating dengue. The use of ultrasonic sensor with infrared light and the incorporation on internet think of are considered capable of repelling and minimizing the spread og the epidemic of dengue mosquitos and insects and is asafe way for excessive use of insecticides and diesel fuel and will later damage the environmental cycle around the home when eradicting dengue fever